OP0027 Abnormal B Cell Activation through Cellular Metabolic Reprogramming and Its Relevance To The Pathogenesis of SLE. (15th July 2016) - Torigoe, M.; Iwata, S.; Sakata, K.; Nakayamada, S.; Tanaka, Y.
Abstract : Background: B cells play a pivotal role in autoimmune diseases. In SLE, IFN signature is displayed and aberrant function of Toll-like receptors (TLR) for recognizing nucleic acids contributes to its pathology. Peripheral plasmablasts increase in active SLE, but the relevance of cellular metabolisms to B cell differentiation to plasmablasts remains unclear. Objectives: To examine the mechanism by which cellular metabolic reprogramming regulates human B cell differentiation in vitro, and its involvement in pathological processes of SLE. Methods: Human B cells were obtained from peripheral blood of healthy donors (HDs), and separated into 3 subsets; naïve (IgD + CD27 – ), IgM memory (IgD + CD27 + ) and class-switched (CS) memory B cells (IgD – CD27 + ). Each subset was cultured with CpG DNA (ligand of TLR9) and/or IFN-α. Plasmablast (CD27 hi ) differentiation, immunoglobulin (IgM, IgG), and cytokine production (IL-6, IL-10), and cellular metabolism (mTORC1, AMPK, glycolysis) were assessed. Results: When IgM memory B cells and CS memory B cells were stimulated with CpG, robust production of IL-6 and IL-10 as well as differentiation to plasmablasts were induced. The gene expression of IRF4, XBP1 and PRDM1 was increased by CpG, whereas that of BACH2 and BCL6 was decreased. These responses were amplified by IFN-α, which was abrogated by anti-IFNAR2 Abs. A JAK inhibitor tofacitinib did not attenuate CpG-induced B cell differentiation to plasmablasts, indicating that JAK-mediated signaling by autocrine IL-6 and IL-10 was not relevant to the differentiation. Next, we analyzed cellular metabolic reprogramming during B cell differentiation, which was recently highlighted for its involvement in T cell differentiation. CpG stimulation strongly induced p-mTORC1 and lactic acid production, indicating that there is a metabolic shift to glycolysis in B cells. IFN-α further augmented this pathway. However, a glycolysis inhibitor, 2-deoxy-D-glucose and an mTORC1 inhibitor, rapamycin significantly abrogated lactic acid production, cytokine production and plasmablast differentiation of B cells in a dose-dependent manner. AMPK activators, metformin and AICAR, which are known to indirectly inhibit mTORC1, not only suppressed plasmablast differentiation but also induced IgD – CD27 – memory B cells. These results indicate that CpG and IFN-α shifted mTORC1/AMPK balance toward mTORC1 activation and glycolysis, leading to plasmablast differentiation. Interestingly, p-mTORC1 was significantly enhanced in B cells of SLE patients, compared to HDs (p<0.05), and it positively correlated with percentage of peripheral plasmablasts (r =0.709, p<0.01) and SLEDAI score (r =0.453, p<0.05), and negatively correlated with CH50 (r = -0.452, p<0.05). Conclusions: CpG and IFN-α shifted mTORC1/AMPK balance toward mTORC1 activation and glycolysis, resulting in plasmablast differentiation, especially in memory B cells. The metabolic shift to anabolism supplied sufficient proteins and nucleic acids for rapid cell proliferation, permitting efficient differentiation to plasmablasts. Abnormal B cell activation through cellular metabolic reprogramming could contribute to SLE pathology. Thus, we first propose the disturbance of "immunometabolism" in B cells, and the regulation of B cell metabolism can provide a new therapeutic strategy against SLE. Disclosure of Interest: M. Torigoe: None declared, S. Iwata: None declared, K. Sakata Employee of: Mitsubishi Tanabe Pharma, S. Nakayamada: None declared, Y. Tanaka Grant/research support from: Mitsubishi-Tanabe, Takeda, Chugai, Astellas, Eisai, Taisho-Toyama, Kyowa-Kirin, Abbvie, Bristol-Myers, Consultant for: Abbvie, Daiichi-Sankyo, Chugai, Takeda, Mitsubishi-Tanabe, Bristol-Myers, Astellas, Eisai, Janssen, Pfizer, Asahi-kasei, Eli Lilly, GlaxoSmithKline, UCB, Teijin, MSD, Santen, Speakers bureau: Abbvie, Daiichi-Sankyo, Chugai, Takeda, Mitsubishi-Tanabe, Bristol-Myers, Astellas, Eisai, Janssen, Pfizer, Asahi-kasei, Eli Lilly, GlaxoSmithKline, UCB, Teijin, MSD, Santen